Spontaneous Breakaway of Tractional Flap Tear during Acute Posterior Vitreous Detachment after Laser Retinopexy - V. A. Shaimova; V. N. Trublin; G. R. Islamova; S. Kh. Kuchkildina; T. B. Shaimov; R. B. Shaimov; T. G. Kravchenko; S. V. Titova (Oftalʹmologiâ, 2022)
Flap tears in the peripheral retina are the most dangerous for the occurrence of regmatogenous retinal detachment (61–83 %), as they are always the result of dynamic vitreoretinal traction. The main method of preventing of regmatogenous retinal detachment in patients with flap tears is laser treatment. Prophylactic laser retinopexy is performed to create an area of sufficient chorioretinal adhesion completely surrounding the retinal break. Currently, the method of non-contact navigated laser retinopexy is widely used. It is safe and well-tolerated procedure equally effective to traditional laser coagulation. The reason for the progression of retinal detachment, which occurs despite preventive therapy, may be insufficient fusion around the retinal break, or the active traction force during the progression of posterior vitreous detachment (PVD). The method of flap retinotomy using modern YAG laser systems with coaxial illumination have been reported in the literature, but there are no publications on spontaneous breakaway of tractional flap tear during acute PVD progression. The case of spontaneous breakaway of tractional flap tear during acute posterior vitreous detachment after laser retinopexy is presented. A 55-year-old woman complained of floaters and photopsias in her left eye within a day. Multimodal examination was performed: visometry, perimetry, scanning laser ophthalmoscopy, ultrasound B-scanning, optical coherence tomography of the retina, fundus photoregistration. Laser treatment was performed with the Navilas Laser System 577s using the non-contact ncPRP lens.Results: The examination revealed a flap tear in the upper nasal segment with subretinal fluid around and spot hemorrhage. Preventive non-contact laser coagulation of the retina was performed in six rows together along the entire border of the tear. 11 days after the operation, the patient applied again with complaints of increased photopsias within a day. During the examination, spontaneous breakaway of the flap from the base, complete retinal attachment, absence of intraocular hemorrhage were revealed.Conclusion: Timely diagnosis and preventive laser retinopexy of peripheral retinal flap tear contributed to the prevention of development of the rhegmatogenous retinal detachment